The big cheese - John, Jory; Oswald, Pete (New York, NY : Harper, 2023)
The Big Cheese is the best at everything, and brags about it, too. When the annual Cheese-cathlon comes around, the Big Cheese is prepared to win, as always. But what happens when the quiet new kid, Wedge Wedgeman, comes out on top? Is a slice of humility all the Big Cheese needs to discover that some things are better than being the best?
2.4
K-3
AD420L
Keywords: Friendship -- Juvenile fiction; Cheese -- Juvenile fiction; Sportsmanship -- Juvenile fiction; Humility -- Juvenile fiction; Friendship -- Fiction; Cheese -- Fiction; Sportsmanship -- Fiction; Humility -- Fiction